2016
DOI: 10.1093/nar/gkw648
|View full text |Cite
|
Sign up to set email alerts
|

Length heterogeneity at conserved sequence block 2 in human mitochondrial DNA acts as a rheostat for RNA polymerase POLRMT activity

Abstract: The guanine (G)-tract of conserved sequence block 2 (CSB 2) in human mitochondrial DNA can result in transcription termination due to formation of a hybrid G-quadruplex between the nascent RNA and the nontemplate DNA strand. This structure can then influence genome replication, stability and localization. Here we surveyed the frequency of variation in sequence identity and length at CSB 2 amongst human mitochondrial genomes and used in vitro transcription to assess the effects of this length heterogeneity on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 57 publications
1
33
0
Order By: Relevance
“…However, CSB II showed variations relating to mutational hotspots at positions 301 (C insertion), 309 (C insertion), 310 (T>C) and 315 (C insertion and C deletion). This is consistent with previous reports, which indicated that variations primarily occur in CSB II (26,61,(62)(63)(64)(65) and are associated with errors in transcription (63), which can result in the occurrence or progression of diseases such as cancer (65). In the present study, a higher number of mutations occurring at positions 303-315 were observed in the controls (86 variations) compared with patients (76 variations), contradicting previous reports of mutations within the D310 region being associated with cancer (26,65,(68)(69)(70).…”
Section: Haplotypesupporting
confidence: 88%
“…However, CSB II showed variations relating to mutational hotspots at positions 301 (C insertion), 309 (C insertion), 310 (T>C) and 315 (C insertion and C deletion). This is consistent with previous reports, which indicated that variations primarily occur in CSB II (26,61,(62)(63)(64)(65) and are associated with errors in transcription (63), which can result in the occurrence or progression of diseases such as cancer (65). In the present study, a higher number of mutations occurring at positions 303-315 were observed in the controls (86 variations) compared with patients (76 variations), contradicting previous reports of mutations within the D310 region being associated with cancer (26,65,(68)(69)(70).…”
Section: Haplotypesupporting
confidence: 88%
“…Thus, the more commonly occurring sequences - G6AG8 and G6AG7 (30% of the population) - exhibit significantly higher efficiency of termination as compared to the relatively rare G5AG8 and G5AG6 sequences (Kang et al, 2016; Tan et al, 2016). This suggests that the strength of the G-quadruplex is likely a primary contributor to the efficiency of transcription termination and thus to replication and maintenance of mtDNA copy number (Agaronyan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Our data show that POLRMT and TFB2M variants interact with variants in MT-ND2 and affect BMI. POLRMT and TFB2M are genes that act in concert to perform mitochondrial transcription and replication thus variation within their sequence, and simultaneously in the mitochondrial DNA sequence, can have an influence on mitochondrial and gene copy number as well as influence efficacy of the two processes [ 66 68 ]. Since it is very difficult to assess the significance of such interactions we also looked into all interactions of MT-ND2 variants and checked whether nuclear variants which interacted with mitochondrial MT-ND2 gene were listed as significant in any GWAS study performed until today, as we believed this would strengthen our findings.…”
Section: Discussionmentioning
confidence: 99%